The role of communication in management decision-making in manufacturing enterprises - Qerimaj–Lushtaku, Shehide; Bellaqa, Bashkim (Edelweiss Applied Science and Technology, 2025)
The primary aim of this research is to evaluate the influence of communication on managerial decision-making within manufacturing firms in Kosovo. Employing a quantitative research methodology, the study utilizes statistical analysis of both primary survey data and secondary data sources. According to official records from the Statistical Agency of Kosovo, there were 6,374 registered manufacturing enterprises in 2023, highlighting the sector's significant contribution to the national economy. The empirical results demonstrate that communication clarity (B = .310, p = .006), perception of communication (B = .532, p = .000), and organizational barriers (B = .218, p = .026) have a statistically significant impact on the quality of managerial decisions. The findings suggest that transparent and well-structured communication enhances decision-making effectiveness, whereas operational challenges such as poor coordination, technological limitations, and limited engagement of internal stakeholders hinder the decision process. The study emphasizes that effective communication is integral to managerial decision-making, and strengthening both vertical and horizontal communication channels is crucial. Practically, the results recommend that managers develop comprehensive communication systems involving all relevant stakeholders to foster collaboration, minimize barriers, and improve decision quality in manufacturing organizations.